Lassa Fever Induced Hearing Loss: The Neglected Disability of Hemorrhagic Fever. (November 2020) - Ficenec, Samuel C.; Percak, Jeffrey; Arguello, Sara; Bays, Alison; Goba, Augustine; Gbakie, Michael; Shaffer, Jeffrey G.; Emmett, Susan D.; Schieffelin, John S.; Bausch, Daniel
Highlights: We present the first data derived from audiometric exams of Lassa fever survivors. 17% of Lassa fever survivors reported hearing loss. Bilateral hearing loss was most common among Lassa fever survivors. Abstract: Objective: Lassa fever (LF) a hemorrhagic fever endemic to Western has an incidence of approximately 500, 000 cases per year. Here, we evaluate hearing loss and other sequelae following LF. Methods: This case-control study enrolled laboratory confirmed LF survivors, non-LF Febrile controls and Matched Community controls with no history of LF or recent hospitalization for a febrile illness. Study participants completed a symptom questionnaire. Pure-tone audiometry was completed by a subset of participants. Results: One hundred forty-seven subjects were enrolled aged from 3-66 years (mean = 23.3). LF survivors were significantly more likely to report balance difficulties (55% vs 20%, p < 0.001), hair loss (32% vs 7%, p < 0.001), difficulty speaking (19% vs 1%, p < 0.001), social isolation (50% vs 0%, p < 0.001), and hearing loss (17% vs 1%, p = 0.002) in comparison to Matched-Community Controls. Similar trends were noted in comparison to Febrile Controls, although these findings were non-significant. Fifty subjects completed audiometry. Audiometry found that LF survivors had significantly more bilateral hearing loss in comparison to Matched-Community Controls (30% vs 4%, p = 0.029). Conclusion: This study characterizes the sequelae of LF and highlights the need for increased access to hearing care in West Africa.